PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Meisatila Eriana Putri; Stefanus Christian Relmasira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether or not there is a significant influence of the application of the Realistic Mathematics Education (RME) approach on the mathematics learning outcomes of grade 6 students at SD Kristen 01 Salatiga. This quantitative research with an experimental type uses a research design, namely pretest - posttest with control group design with data collection techniques including observation, interviews, tests, questionnaires, and reflection. Data analysis techniques used include instrument validity and reliability tests, normality tests, homogeneity tests, and paired sample tests. Based on the results of the study, it was found that the application of this approach had a positive and significant influence on improving mathematics learning outcomes and students' critical thinking skills.